Seasonal variation in the thermal biology of a terrestrial toad, Rhinella icterica (Bufonidae), from the Brazilian Atlantic Forest - Anderson, Rodolfo César de Oliveira [UNESP]; Bovo, Rafael Parelli [UNESP]; Andrade, Denis Vieira [UNESP] (Elsevier, 2018)
As ectotherms, amphibians may exhibit changes in their thermal biology associated with spatial and temporal environmental contingencies. However, our knowledge on how amphibian´s thermal biology responds to seasonal changes in the environment is restricted to a few species, mostly from temperate regions, in a marked contrast with the high species diversity found in the Neotropics. We investigated whether or not the seasonal variation in climatic parameters from a high-montane ombrophilous forest in the Brazilian Atlantic Forest could lead to concurrent adjustments in the thermal biology of the terrestrial toad Rhinella icterica. We measured active body temperature (Tb) in the field, and preferred body temperature (Tpref) and thermal tolerance (critical thermal minimum, CTmin, and maximum, CTmax) in the laboratory, for toads collected at two distinct seasons: warm/wet and cold/dry. We also measured operative environmental temperatures (Te) using agar toad models coupled with dataloggers distributed in different microhabitats in the field to estimate accuracy (db) and effectiveness (E) of thermoregulation of the toads for both seasons. Toads had higher Tpref in the warm/wet season compared to the cold/dry season, even though no seasonal change occurred in field Tb's. In the warm/wet season, toads decreased the accuracy of thermoregulation and avoided thermally favorable microhabitats, while in the cold/dry season they increased the accuracy of thermoregulation and exhibited high degree of thermoconformity. This result may encompass thermoregulatory adjustments to seasonal changes in Te's, but may also reflect seasonal differences in compromises between Tb regulation and other ecologically relevant activities (reproduction, foraging). Toads did not exhibit changes in CTmin or CTmax, which indicates a low risk of exposure to extreme temperatures in this particular habitat, at both seasons, possibly combined with a low flexibility of this trait. Overall, our study shows seasonal acclimatization in some aspects of the thermal biology of the toad, R. icterica.
Keywords: Anurans; Operative environmental temperatures; Preferred body temperature; Seasonal acclimatization; Thermal tolerance; Thermoregulatory behavior